Prevalent races of wheat rust pathogens in Lebanon, Morocco, and Tunisia in 2022 - Nazari, Kumarse (2023)
During the 2022 rust surveys in Lebanon, Morocco, and Tunisia (WP1-OP2), rust samples were collected from survey sites. The collected rust samples were submitted to the Regional Cereal Rust Biocontainment Laboratory in Izmir, Turkey using the sampling kits and import permits granted by Turkish quarantine authorities. Viable samples were used in Races analysis. The race analysis confirmed the presence of stem rust races TKKTF and TKTTF in Lebanon and TKKTF, TKTTF, THTTF, and TTTTF in Morocco.